MOBILITAS SOSIAL NELAYAN PASCA SEDIMENTASI DAERAH ALIRAN SUNGAI (DAS) (Studi Kasus: Desa Klaces, Kecamatan Kampung Laut, Kabupaten Cilacap, Provinsi Jawa Tengah) - Agusning Kuwandari, Septi; Satria, Arif (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2012)
The interaction between human and nature will cause many ecological impacts, such as declining environment quality. The relationship between inland and sea can not be separated each other. The inland damaged will affect coastal areas. Sedimentation in Watershed (DAS) make ec ol ogi cal changes , i t’ s accordingly. It can greatly affect the socio-economic conditions of coastal communities. This situation leads the communities to develop strategies adaptation which finally change stratification system and social mobility. Keywords: coastal, sedimentation, social mobility, strategies adaptation, Watershed (DAS)